Detection of Circulating Tumor Cell Subpopulations in Patients with Head and Neck Squamous Cell Carcinoma (HNSCC) - Weller, Patrick (PLoS One, 2014)
BACKGROUND: Since image based diagnostic tools fail to detect early metastasis in head and neck squamous cell carcinoma (HNSCC) it is crucial to develop minimal invasive diagnostic methods. A promising approach is to identify and characterize circulating tumor cells (CTC) in the peripheral blood of HNSCC patients. In this pilot study, we assessed which non-hematopoietic cell types are identifiable and whether their numbers differ in pre- and postoperative blood samples. METHODS: 20 ml citrated peripheral blood was taken from 10 HNSCC patients before and after curative resection. CTC were enriched using density gradient centrifugation. CTC presence was verified by multi-immunofluorescence staining against cytokeratin (CK; epithelial), N-cadherin (mesenchymal); CD133 (stem-cell), CD45 (hematopoietic) and DAPI (nucleus). Individual cell type profiles were analyzed. RESULTS: We were able to detect cells with epithelial properties like CK+/N-cadherin−/CD45− and CK+/CD133−/CD45− as well as cells with mesenchymal features such as N-cadherin+/CK−/CD45− and cells with both characteristics like N-cadherin+/CK+/CD45−. We also observed cells showing stem cell-like features like CD133+/CK−/CD45− and cells with both epithelial and stem cell-like features such as CD133+/CK+/CD45−. The number of CK positive cells (p = 0.002), N-cadherin positive cells (p = 0.002) and CD133 positive cells (p = 0.01) decreased significantly after resection. Kaplan-Meier test showed that the survival was significantly shorter when N-cadherin+ cells were present after resection (p = 0.04; 474 vs. 235 days; [HR] = 3.1). CONCLUSIONS: This is - to the best of our knowledge- the first pilot study identifying different CTC populations in peripheral blood of HNSCC patients and showing that these individual cell type profiles may have distinct clinical implications.